P-660 Polymorphisms in FSHR gene do not affect late follicular phase steroidogenic response in predicted normoresponders. Secondary analysis of a prospective multicenter cohort study. (30th June 2022) - Neves, A.R; Blockeel, C; García, S; Alviggi, C; Spits, C; Ma, P.Q.M; Ho, T.M; Tournaye, H; Vuong, N.L; Polyzos, N.P
Abstract: Study question: Does the presence of FSHR SNPs influence late follicular phase progesterone and estradiol serum levels in predicted normoresponders treated with rFSH? Summary answer: The presence of FSHR SNPs (rs6165, rs6166, rs1394205) had no statistically significant impact on late follicular phase serum progesterone and estradiol levels. What is known already: Previous studies have shown that late follicular phase serum progesterone and estradiol levels are significantly correlated with the magnitude of ovarian response. Several authors have proposed that individual variability in the response to ovarian stimulation could be explained by variants in FSHR . So far, the literature is scarce on the influence of this genetic variability on late follicular phase steroidogenic response. Our aim is to determine whether genetic variants in the FSHR gene could modulate late follicular phase serum progesterone and estradiol levels. Study design, size, duration: We performed a secondary analysis of a multicenter multinational prospective study including 366 patients from Vietnam, Belgium and Spain (166 from Europe and 200 from Asia), conducted from 11/2016-06/2019. All patients underwent ovarian stimulation followed by oocyte retrieval in an antagonist protocol with a fixed daily dose of 150IU rFSH. All patients had a serum progesterone and estradiol measurement on the day of trigger and were genotyped for 3 FSHR SNPs (rs6165, rs6166, rs1394205). Participants/materials, setting, methods: Patients included were predicted normal responder women <38 years old undergoing their first or second ovarian stimulation cycle. The prevalence of late follicular phase elevated serum progesterone (EP), as well as mean serum progesterone and estradiol levels on the day of trigger were compared between the different FSHR SNPs genotypes. EP was defined as > 1.5 ng/ml. Main results and the role of chance: The overall prevalence of EP was 15.8% (n = 58). No significant difference was found in the prevalence of EP in Caucasian and Asian patients (17.5% vs. 14.5%). Genetic model analysis revealed a similar prevalence of EP in co-dominant, dominant and recessive models for variants FSHR rs6166, rs6165 and rs1394205. Also, no statistically significant difference was found in the mean serum progesterone levels in the three genetic models. Likewise, FSHR SNPs genotypes had no statistically significant impact in the mean late follicular phase serum estradiol levels Limitations, reasons for caution: This study is a post-hoc analysis of a multicenter multinational prospective cohort study. The results must be interpreted with caution considering the sample size of the EP group. The fact that a fixed daily dose of 150 IU rFSH was used in this population precludes the generalization of the results. Wider implications of the findings: Based on our results, FSHR SNPs rs6165, rs6166, rs1394205 do not influence late follicular phase serum progesterone nor estradiol levels in predicted normal responders. These findings add to the controversy in the literature regarding the impact of individual genetic susceptibility in response to ovarian stimulation in this population. Trial registration number: not-applicable